Faktor-Faktor yang Mempengaruhi Penyerapan Anggaran Belanja pada Satuan Kerja Perangkat Daerah Dengan Administrasi Sebagai Pemoderasi - Ulandari, Viki; Akram, Akram; Santoso, Budi (E-Jurnal Akuntansi; Vol 31 No 6 (2021), 2021)
This study aims to provide empirically the effect of  planning, human resources, and procurement of goods / services on the absorption of the expenditure budget in the SKPD of Sumbawa Regency and the influence of administration in the relationship between planning, human resources, and procurement of goods / services on the absorption of the expenditure budget in SKPD Sumbawa regency. Population in this research is all employees at 29 SKPD Sumbawa Regency. The results showed that planning had a negative and significant effect on budget absorption. Human resources and the procurement of goods / services have a positive effect on budget absorption. Meanwhile, administration has a negative effect on the relationship between planning, human resources and the procurement of goods / services and budget absorption. Keywords: Absorption Budget; Planning; human Resource; Procurement Of Goods / Services; Administration.